Khat chewing and associated factors among public secondary school students in Harar town, Eastern Ethiopia: a multicenter cross-sectional study - Nigussie, Kabtamu; Negash, Abraham; Sertsu, Addisu; Mulugeta, Abiy; Tamire, Aklilu; Kassa, Obsan; Abdeta, Tilahun; Dereje, Jerman (Frontiers in Psychiatry, 2023)
Background Khat is a huge, evergreen tree that grows at high altitudes throughout the Arabian Peninsula and in the region stretching from eastern to southern Africa. Cathinone, cathine, and norephedrine are psychoactive ingredients contained in khat. Ethiopian teenagers, especially those in secondary school, frequently use khat. This use of khat may lead to students frequently missing class and experiencing subpar academic performance. However, the study area lacks information regarding the prevalence of khat use and the factors associated with it. Objective This study's primary goal is to determine the prevalence of khat chewing and related factors among secondary school students in public schools in Harar, Eastern Ethiopia, in 2022. Methods A multicenter cross-sectional study design was employed from June 01–June 30, 2022, in three public secondary schools in Harar town in a sample of 485 students. Systematic random sampling was used to choose the study sample. Data were gathered using self-administered questionnaires, and the Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) was used to assess khat chewing. Epidata version 4.6 was used to enter the data, while STATA version 14 was used to analyze them. To determine the factors related to khat chewing, bivariate and multivariate logistic regression analysis was conducted, and statistical significance was determined at a 95% confidence level with a P-value under 0.05. Results Out of 485 eligible participants, 455 responded to this survey, giving a response rate of 93.8%. Overall, 33.2% (95% CI: 29.2%−37.6%) of the sample's participants reported currently chewing khat. Age ranged from 20 to 25 years (AOR = 2.04; 95% CI: 1.19–3.48), male students (AOR = 7.03; 95% CI: 4.35–12.57), current alcohol user (AOR 6.48; 95% CI: 2.30–18.28), presence of chewer friends (AOR 3.86; 95% CI: 2.38–6.24), and depression (AOR 1.84, 95%CI: 1.02–3.30), were strongly associated with khat chewing at a p-value of < 0.05. Conclusion Khat chewing was very common among students in Eastern Ethiopia's public secondary schools. Ages between 20 and 25 years, being a male, being current alcohol users, having chewer buddies, and depression are all significantly linked to khat use. Thus, schools should create and implement audience-specific behavioral change communication to deter and stop students from chewing khat. Additionally, it is important to ban the sale of khat to young adults and adolescents, promote medical care for khat users, and foster peer advocacy for support services.